Seasonal differences in aerosol abundance and radiative forcing in months of contrasting emissions and rainfall over northern South Asia. (January 2016) - Sadavarte, P.; Venkataraman, C.; Cherian, R.; Patil, N.; Madhavan, B.L.; Gupta, T.; Kulkarni, S.; Carmichael, G.R.; Adhikary, B.
Abstract: A modeling framework was used to examine gaps in understanding of seasonal and spatial heterogeneity in aerosol abundance and radiative forcing over northern South Asia, whose glimpses are revealed in observational studies. Regionally representative emissions were used in chemical transport model simulations at a spatial resolution of 60 × 60 km 2, in April, July and September, chosen as months of contrasting emissions and rainfall. Modeled aerosol abundance in northern South Asia was predominantly found to be dust and carbonaceous in April, dust and sulfate in July and sulfate and carbonaceous in September. Anthropogenic aerosols arose from energy-use emissions (from industrial sources, residential biofuel cooking, brick kilns) in all months, additionally from field burning in April, and incursion from East Asia in September. In April, carbonaceous aerosols were abundant from open burning of agricultural fields even at high altitude locations (Godavari), and of forests in the eastern Gangetic Plain (Kolkata). Direct radiative forcing and heating rate, calculated from OPAC-SBDART, using modeled aerosol fields, and corrected by MODIS AOD observations, showed regionally uniform atmospheric forcing in April, compared to that in other months, influenced by both dust and black carbon abundance. A strong spatial heterogeneity of radiative forcing and heating rate was found, with factor of 2.5–3.5 lower atmospheric forcing over the Tibet plateau than that over the Ganga Plain and Northwest in July and September. However, even over the remote Tibet plateau, there was significant anthropogenic contribution to atmospheric forcing and heating rate (45% in Apr, 75% in Sep). Wind fields showed black carbon transport from south Asia in April and east Asia in September. Further evaluation of the transport of dust and anthropogenic emissions from various source regions and their deposition in the Himalaya and Tibet, is important in understanding regional air quality and climate change over this ecosystem. Highlights: WRF-STEM simulations show larger BC and OC burden in Apr, SO4 in Jul & Sep. Influence of agricultural field burning in Apr, incursion from East Asia in Sep. Aerosol atmospheric forcing of 32–48 W m −2, lower in Sep than in Apr & Jul. Anthropogenic fraction of atmospheric forcing, 45–74% over Ganga plain and Tibet. BC transport to Tibet, at elevated levels, from S Asia in Apr & E Asia in Sep.